Pediatric renal transplantation: comparative study with renal transplantation in the adult population - Parada, B (2005)
PURPOSE: To retrospectively review our experience with pediatric renal transplantation and to compare the results with the adult population. PATIENTS AND METHODS: Between January 1981 and August 2003, 74 renal transplants were performed in patients < or =18 years at the time of the transplant--the pediatric group versus 1153 patients in the adult group. We analyzed various risk factors for actuarial kidney graft and patient survivals using the Kaplan-Meier method. RESULTS: Median ages were 13.8 +/- 3.5 and 42.6 +/- 2.4 years, respectively. There was no statistically significant difference in the human leukocyte antigen matching or immunosuppression. There was, however, a younger donor age and shorter ischemia time in the pediatric group. Overall, kidney transplant survival rates for patients < or =18 years at 1, 2, 5, and 10 years were 94.4%, 91.3%, 70.6%, and 58.2%, respectively, with no significant difference for patients older than 18 (91.2%, 89.3%, 78.8%, 60.5%, P = .4325). There was a significantly decreased graft survival in the adult group at 10 years when the donor age was over 60 years and when the ischemia time was > or =20 hours. The incidence of delayed graft function and the creatinine levels of functioning grafts did not differ between the two groups. During the follow-up, acute rejections were more frequent in the younger group. Patient survival in the pediatric group at 1, 2, 5, and 10 years was 98.6%, 98.8%, 98.6%, and 90.3%, respectively, significantly lower in the adult group (95.3%, 94.0%, 87.9%, 76.8%, P < .02). CONCLUSIONS: Renal transplantation may be successfully performed in the pediatric patients with end-stage renal disease. Overall graft survival at 10 years did not differ significantly between the two groups. There is a higher incidence of acute rejections but longer patient survival in the pediatric population